Comparison of long-term cardiovascular and renal outcomes between percutaneous coronary intervention and coronary artery bypass grafting in multi-vessel disease with chronic kidney disease - Kwon, Woochan; Choi, Ki Hong; Jeong, Dong Seop; Lee, Sang Yoon; Lee, Joo Myung; Park, Taek Kyu; Yang, Jeong Hoon; Hahn, Joo-Yong; Choi, Seung-Hyuk; Chung, Su Ryeun; Cho, Yang Hyun; Sung, Kiick; et al. (Frontiers in Cardiovascular Medicine, 2022)
Objective: This study aims to analyze cardiac and renal outcomes of chronic kidney disease(CKD) patients with multi-vessel disease who have undergone coronary artery bypass grafting(CABG) or percutaneous coronary intervention(PCI). Methods: CKD patients with multi-vessel disease who underwent CABG or PCI were retrospectively selected from our database and divided into the PCI group(further stratified into PCI with complete revascularization[PCI-CR] and incomplete revascularization[PCI-IR] groups) and the CABG group. The primary endpoint was the composite of all-cause death, myocardial infarction(MI), or stroke at 5 years. Key secondary endpoint was the 5-year rate of the renal composite outcome, defined as >40% glomerular filtration rate decrease, initiation of dialysis, and/or kidney transplant. Outcomes were compared using Cox proportional hazards regression analysis, and the results were further adjusted by multivariable analyses and inverse-probability-weighting. Results: Among the study population (n=798), 443 (55.5%) patients received CABG and 355 (44.5%) patients received PCI. Compared with the CABG group, the PCI group had similar risk of the primary endpoint (CABG vs. PCI, 19.3% vs. 24.0%, HR:1.28, 95%CI: 0.95-1.73, p=0.11) and a lower risk of the renal composite outcome (36.6% vs. 31.2%, HR:0.74, 95%CI 0.58-0.94, p=0.03). Additionally, PCI-IR was associated with a significantly higher risk of the primary endpoint compared with CABG (HR:1.54, 95%CI: 1.11-2.13, p=0.009) or PCI-CR (HR:1.78, 95%CI: 1.09-2.89, p=0.02). However, PCI-CR had a comparable 5-year death, MI or stroke rate to CABG (HR:0.86, 95%CI 0.54-1.38, p=0.54). Conclusions: CABG showed similar incidence of death, MI or stroke compared to PCI but was associated with a higher risk of renal injury. PCI-CR had a prognosis comparable to that of CABG while PCI-IR had worse prognosis. If PCI is chosen for revascularization in CKD patients, achieving CR should be attempted to ensure favorable outcomes.